Distinct roles of Constitutive Photomorphogenesis Protein 1 homolog (COP1) in human hepatocyte models - Sébastien Soubeyrand; Paulina Lau; Ruth McPherson; Ruth McPherson (Frontiers in Molecular Biosciences)
IntroductionConstitutive Photomorphogenesis Protein 1 homolog (COP1) is a conserved E3 ligase with key roles in several biological systems. Prior work in hepatocyte-derived tumors categorized COP1 as an oncogene, but its role in untransformed hepatocytes remains largely unexplored. Here, we have investigated the role of COP1 in primary human hepatocytes and two transformed hepatocyte models, HepG2 and HuH-7 cells.MethodsThe role of COP1 was tested by silencing and transduction experiments in HepG2, HuH-7, and primary human hepatocytes. Transcription array data of COP1-suppressed cells were generated and analyzed using clustering analyses. Cellular impacts were examined by proliferation assays, qRT-PCR, western blotting, reporter assays, and APOB enzyme-linked immunosorbent assays.Results and DiscussionCOP1 suppression had no noticeable impact on HepG2 and HuH-7 proliferation and was associated with contrasting rather than congruent transcriptome changes. Transcriptomic changes were consistent with perturbed metabolism in primary hepatocytes and HepG2 cells and impaired cell cycle regulation in HuH-7 cells. In HepG2 and primary hepatocytes but not in HuH-7 cells, COP1 suppression reduced the expression of important hepatic regulators and markers. COP1 downregulation reduced hepatic nuclear factor-4 alpha (HNF4A) abundance and function, as assessed by a lower abundance of key HNF4A targets, reduced APOB secretion, and reporter assays. HNF4A function could be restored by introducing a siRNA-resistant COP1 transgene, whereas HNF4A restoration partially rescued COP1 silencing in HepG2 cells. Our results identify and detail a pivotal regulatory role of COP1 in hepatocytes, in part through HNF4A.